Public Service Innovation at Regency Public Service Malls South Lampung - Apriza, Tiyas; Tomy, Chairian Tomy (Universitas Indonesia Mandiri, 2025)
In an effort to streamline public services and increase their efficiency, South Lampung Regency formally introduces the Public Service Mall. This Public Service Mall is located near officially opened on Monday, December 5, 2023, by the Menpan RB. The public management theory employed in this study refers to a set of procedures, policies, and initiatives meant to effectively and efficiently manage public resources. Aspects of the public sector include funds, personnel, infrastructure, data, and other types of government-owned assets. Public management's primary objective is to allocate and coordinate these resources as efficiently as possible to meet the many demands of society and have a positive impact on it. The methodology used in this study is qualitative. Researchers start their investigations. This is accomplished through observation, which is followed by support and interviews, with supporting documentation. Using purposive sampling, the researchers identified 5 informants, 4 support informants and 1 key informant. The infrastructure and amenities offered by South Lampung Regency Public Services' malls are highly comprehensive. There appear to be existing amenities for those with disabilities (road obstacles), a lactation area, a playground, and a reading nook.